A MENNONITE PERSPECTIVE OF HOSPITALITY IN TIMES OF MIGRATIONS - Kim Sun, Hyung (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2020)
From their beginning, Mennonites have experienced forced migrations due to religious persecution. Based on their migration experiences, biblical interpretations, and theological understandings of the church and the state, I offer a Mennonite perspective of hospitality that includes five core aspects. First, wherever we live and dwell, that space is the Lord’s and God is the ultimate host who welcomes anyone in God’s place. Second, as a migrant, wherever one might arrive, that place is God’s providence, whether it is temporary or long-term. Third, as a host, whoever might arrive at one’s place, the guests are God’s people. Fourth, hospitality means to mutually and joyfully share God’s abundant gifts that God has given both to the hosts and the guests. Fifth, as the church truly practice hospitality, we become a signpost of the kingdom of God, an alternative community that goes beyond our dominant ideologies, like capitalism and nationalism.